Megacapitula guizhouensis (Megacapitulaceae, Pleosporales), a new species from Guizhou Province, China - Zhao, Gui-Li; Liu, Ning-Guo; Lu, Yong-Zhong; Xiao, Xing-Juan; Liu, Ying; Luo, Li-Juan; Samarakoon, Milan C. (Phytotaxa, 2026)
A new hyphomycetous species, Megacapitula guizhouensis, collected from a forest in Guizhou Province, China, is described and illustrated. The species is characterized by micronematous conidiophores and solitary, tadpole-shaped, dark brown to black conidia, which exhibit long, dense, hairy appendages arising from a beak-like apical structure. Phylogenetic analyses based on the combined large subunit ribosomal RNA region (LSU), internal transcribed spacer region (ITS), small subunit ribosomal RNA region (SSU), translation elongation factor 1-alpha (tef1-α) and RNA polymerase II second largest subunit (rpb2) sequences indicate that M. guizhouensis is sister to the type species M. villosa with strong statistical support (100% ML/1.00 PP). The morphologically similar genus Kalamarospora is compared and discussed.